The Impact of Glass Material on Growth and Biocatalytic Performance of Mixed-Species Biofilms in Capillary Reactors for Continuous Cyclohexanol Production - Heuschkel, Ingeborg; Dagini, Rakesh; Karande, Rohan; Bühler, Katja (Frontiers in Bioengineering and Biotechnology, 2020)
In this study, the growth and catalytic performance of mixed-species biofilms consisting of photoautotrophic Synechocystis sp. PCC 6803 and chemoheterotrophic Pseudomonas sp. VLB120 was investigated. Both strains contained a cytochrome P450 monooxygenase enzyme system catalyzing the oxyfunctionalization of cyclohexane to cyclohexanol. Biofilm cultivation was performed in capillary glass reactors made of either, borosilicate glass (Duran) or quartz glass, in different flow regimes. Consequently, four phases could be distinguished for mixed-species biofilm growth and development in the glass-capillaries. The first phase represents the limited growth of mixed-species biofilm in the single-phase flow condition. The second phase includes a rapid increase in biofilm spatial coverage after the start of air-segments. The third phase starts with the sloughing of large biofilm patches from well-grown biofilms, and the final stage consists of biofilm regrowth and the expansion of the spatial coverage. The catalytic performance of the mixed-species biofilm after the detachment process was compared to a well-grown biofilm. With an increase in the biofilm surface coverage, the cyclohexanol production rate improved from 1.75 to 6.4 g m-2 d-1, resulting in comparable production rates to the well-grown biofilms. In summary, high productivities can be reached for biofilms cultivated in glass capillaries, but stable product formation was disturbed by sloughing events.